Elucidating the individual effects of calcium and phosphate ions on hMSCs by using composite materials. (15th April 2015) - Danoux, Charlène B.S.S.; Bassett, David C.; Othman, Ziryan; Rodrigues, Ana I.; Reis, Rui L.; Barralet, Jake E.; van Blitterswijk, Clemens A.; Habibovic, Pamela
Graphical abstract: Abstract: The biological performance of bone graft substitutes based on calcium phosphate bioceramics is dependent on a number of properties including chemical composition, porosity and surface micro- and nanoscale structure. However, in contemporary bioceramics these properties are interlinked, therefore making it difficult to investigate the individual effects of each property on cell behavior. In this study we have attempted to investigate the effects of calcium and inorganic phosphate ions independent from one another by preparing composite materials with polylactic acid (PLA) as a polymeric matrix and calcium carbonate or sodium phosphate salts as fillers. Clinically relevant bone marrow derived human mesenchymal stromal cells (hMSCs) were cultured on these composites and proliferation, osteogenic differentiation and ECM mineralization were investigated with time and were compared to plain PLA control particles. In parallel, cells were also cultured on conventional cell culture plates in media supplemented with calcium or inorganic phosphate to study the effect of these ions independent of the 3D environment created by the particles. Calcium was shown to increase proliferation of cells, whereas both calcium and phosphate positively affected alkaline phosphatase enzyme production. QPCR analysis revealed positive effects of calcium and of inorganic phosphate on the expression of osteogenic markers, in particular bone morphogenetic protein-2 and osteopontin. Higher levels of mineralization were also observed upon exposure to either ion. Effects were similar for cells cultured on composite materials and those cultured in supplemented media, although ion concentrations in the composite cultures were lower. The approach presented here may be a valuable tool for studying the individual effects of a variety of soluble compounds, including bioinorganics, without interference from other material properties.